Difference between revisions of "Double angle formulas"

(Blanked the page)
(Tag: Blanking)
Line 1: Line 1:
This unit looks at trigonometric formulae known as the double angle formulae. They are called
 
this because they involve trigonometric functions of double angles, i.e. sin 2A, cos 2A and tan2A.
 
In order to master the techniques explained here it is vital that you undertake the practice
 
exercises provided.
 
  
 
 
After reading this text, and/or viewing the video tutorial on this topic, you should be able to:
 
• derive the double angle formulae from the addition formulae
 
• write the formula for cos 2A in alternative forms
 
• use the formulae to write trigonometric expressions in different forms
 
• use the formulae in the solution of trigonometric equations
 
 
 
 
Contents
 
1. Introduction 2
 
2. The double angle formulae for sin 2A, cos 2A and tan2A 2
 
3. The formula cos2A = cos2 A − sin2 A 3
 
4. Finding sin3x in terms of sin x 3
 
5. Using the formulae to solve an equation 4
 
1. Introduction
 
This unit looks at trigonometric formulae known as the double angle formulae. They are called
 
this because they involve trigonometric functions of double angles, i.e. sin 2A, cos 2A and tan2A.
 
2. The double angle formulae for sin 2A, cos 2A and tan 2A
 
We start by recalling the addition formulae which have already been described in the unit of the
 
same name.
 
sin(A + B) = sin A cos B + cos A sin B
 
cos(A + B) = cos A cos B − sin A sin B
 
tan(A + B) = tan A + tan B
 
1 − tan A tan B
 
We consider what happens if we let B equal to A. Then the first of these formulae becomes:
 
sin(A + A) = sin A cos A + cos A sin A
 
so that
 
sin 2A = 2 sin A cos A
 
This is our first double-angle formula, so called because we are doubling the angle (as in 2A).
 
Similarly, if we put B equal to A in the second addition formula we have
 
cos(A + A) = cos A cos A − sin A sin A
 
so that
 
cos 2A = cos2 A − sin2 A
 
and this is our second double angle formula.
 
Similarly
 
tan(A + A) = tan A + tan A
 
1 − tan A tan A
 
so that
 
tan 2A =
 
2 tan A
 
1 − tan2 A
 
These three double angle formulae should be learnt.
 
3. The formula cos 2A = cos2 A − sin2 A
 
We now examine this formula more closely.
 
We know from an important trigonometric identity that
 
cos2 A + sin2 A = 1
 
so that by rearrangement
 
sin2 A = 1 − cos2 A.
 
So using this result we can replace the term sin2 A in the double angle formula. This gives
 
cos 2A = cos2 A − sin2 A
 
= cos2 A − (1 − cos2 A)
 
= 2 cos2 A − 1
 
This is another double angle formula for cos 2A.
 
Alternatively we could replace the term cos2 A by 1 − sin2 A which gives rise to:
 
cos 2A = cos2 A − sin2 A
 
= (1 − sin2 A) − sin2 A
 
= 1 − 2 sin2 A
 
which is yet a third form.
 
4. Finding sin 3x in terms of sin x
 
Example
 
Consider the expression sin 3x. We will use the addition formulae and double angle formulae to
 
write this in a different form using only terms involving sin x and its powers.
 
We begin by thinking of 3x as 2x + x and then using an addition formula:
 
sin 3x = sin(2x + x)
 
= sin 2x cos x + cos 2x sin x using the first addition formula
 
= (2 sin x cos x) cos x + (1 − 2 sin2 x) sin x using the double angle formula
 
cos 2x = 1 − 2 sin2 x
 
= 2 sin x cos2 x + sin x − 2 sin3 x
 
= 2 sin x(1 − sin2 x) + sin x − 2 sin3 x from the identity cos2 x + sin2 x = 1
 
= 2 sin x − 2 sin3 x + sin x − 2 sin3 x
 
= 3 sin x − 4 sin3 x
 
We have derived another identity
 
sin 3x = 3 sin x − 4 sin3 x
 
Note that by using these formulae we have written sin 3x in terms of sin x (and its powers). You
 
could carry out a similar exercise to write cos 3x in terms of cos x.
 
5. Using the formulae to solve an equation
 
Example
 
Suppose we wish to solve the equation cos 2x = sin x, for values of x in the interval −π ≤ x < π.
 
We would like to try to write this equation so that it involves just one trigonometric function, in
 
this case sin x. To do this we will use the double angle formula
 
cos 2x = 1 − 2 sin2 x
 
The given equation becomes
 
1 − 2 sin2
 
x = sin x
 
which can be rewritten as
 
0 = 2 sin2 x + sin x − 1
 
This is a quadratic equation in the variable sin x. It factorises as follows:
 
0 = (2 sin x − 1)(sin x + 1)
 
It follows that one or both of these brackets must be zero:
 
2 sin x − 1 = 0 or sin x + 1 = 0
 
so that
 
sin x =
 
1
 
2
 
or sin x = −1
 

Revision as of 03:09, 1 August 2019

Invalid username
Login to AoPS